A STUDY OF PROGNOSTIC FACTORS OF ACUTE LIMB ISCHEMIA - Kumar, Deepak; Hoda, Ilmul; Paswan, Nirmal; Haseen, Azam (Student's Journal of Health Research Africa, 2024)
Background: Acute limb ischemia (ALI) is a sudden reduction in limb perfusion that threatens limb viability and requires urgent intervention. Objectives: To evaluate prognostic factors influencing outcomes in patients with ALI undergoing surgical revascularization. Materials and Methods: This prospective study was conducted over two years at JNMCH, AMU, Aligarh, involving 28 patients diagnosed with ALI. Clinical data, risk factors, etiology, Rutherford classification, surgical procedures, and postoperative outcomes were recorded and analyzed. Results: The majority of patients were male (85.7%) with a mean age of 39.5 years. Thromboembolism (67.9%) was the most common cause, and Rutherford class IIa was the most frequent presentation (64.3%). Risk factors included diabetes (46.4%), smoking (42.9%), and hypertension (39.3%). Limb salvage was achieved in 85.7% of cases, while 14.3% required amputation. Early intervention was associated with better functional outcomes. Conclusion: Prompt diagnosis and timely surgical management significantly improve limb salvage in ALI. Identification and control of modifiable risk factors are essential to prevent disease progression and reduce amputation rates.